Effects of foot progression angle on kinematics and kinetics of a cutting movement - Kohei Nishizawa; Takeshi Hashimoto; Satoshi Hakukawa; Takeo Nagura; Toshiro Otani; Kengo Harato (Journal of Experimental Orthopaedics)
Abstract Purpose Foot progression angle is a key factor for biomechanical knee load, which is associated with noncontact anterior cruciate ligament (ACL) injury during sports‐specific tasks. The purpose of the present study was to assess the biomechanics of trunk, pelvis, and lower extremities during a cutting maneuver under different foot progression angles. Methods Nineteen male collegiate athletes (ages 18–24) participated in the present study. Cutting motion was analyzed using eight infrared cameras (250 Hz), two force plates (1250 Hz), and 44 reflective markers. Subjects performed 45‐degree side cutting maneuvers under three foot progression angles, including 20 degrees (toe‐out: TO), 0 degrees (neutral: TN), and − 20 degrees (toe‐in: TI). Peak values of each biomechanical parameters in trunk, pelvis, hip, and knee within a first 40% stance phase and each parameter at the timing of the peak vertical ground reaction force were assessed. A statistical analysis was performed to compare data among the three‐foot progression angles using the Friedman test. Results Peak angles of knee abduction, tibial internal rotation, hip internal rotation, and hip adduction were significantly greater for TI position than for TO position (p < 0.01). Peak moments of knee abduction and tibial internal rotation under TI position were also significantly larger than TO position (p < 0.01). Moreover, greater peak pelvis‐trunk rotation was found for TI position than for TN and TO positions (p < 0.01). Conclusion From the present study, TI position could lead to an increased risk of ACL injury during a pre‐planned cut maneuver, compared to TO position.